The Relationship Between Passion for Life and Passion and Indifference Toward Sexual Relations in Married Students - Mohammadi, Fatemeh Hana; Mirzaian , Bahram (KMAN Counseling & Psychology Nexus, 2025)
This study aimed to examine the relationship between passion for life and both passion and indifference toward sexual relations among married students. The research employed a descriptive-correlational design. The study population consisted of all married students enrolled in the Faculty of Engineering at the Islamic Azad University, Sari Branch, during the 2023–2024 academic year. A sample of 98 married students was selected through convenient (non-random) sampling. Data were collected using the Emotional Orientation to Sexual Relations Questionnaire, which measures sexual fear, passion, and indifference, and the Passion for Life Questionnaire. Both instruments have demonstrated high internal consistency reliability, with Cronbach’s alpha coefficients of 0.97 and 0.98, respectively. Data were analyzed using Spearman’s non-parametric correlation test in SPSS version 26. The analysis revealed significant positive correlations between passion for life and both passion toward sexual relations (r = 0.33, p < .05) and indifference toward sexual relations (r = 0.36, p < .05). These results indicate that individuals reporting greater passion for life also tend to show stronger emotional engagement, but at the same time may experience ambivalent or indifferent sexual orientations. Gender differences were observed, with men generally reporting slightly higher levels of passion for life compared to women, though the correlations were consistent across genders. The findings suggest a complex interplay between general life enthusiasm and emotional approaches to sexual relationships. This study highlights the significant associations between passion for life and the emotional orientation toward sexual relations in married students. Understanding these links can inform psychological and marital counseling interventions aimed at enhancing both life engagement and sexual well-being. The results emphasize the importance of considering overall vitality and passion when addressing sexual relationship dynamics in couples.